Assessing rare earth elements in quartz rich geological samples. (January 2016) - Santoro, A.; Thoss, V.; Ribeiro Guevara, S.; Urgast, D.; Raab, A.; Mastrolitti, S.; Feldmann, J.
Abstract: Sodium peroxide (Na2 O2 ) fusion coupled to Inductively Coupled Plasma Tandem Mass Spectrometry (ICP-MS/MS) measurements was used to rapidly screen quartz-rich geological samples for rare earth element (REE) content. The method accuracy was checked with a geological reference material and Instrumental Neutron Activation Analysis (INAA) measurements. The used mass-mode combinations presented accurate results (only exception being 157 Gd in He gas mode) with recovery of the geological reference material QLO-1 between 80% and 98% (lower values for Lu, Nd and Sm) and in general comparable to INAA measurements. Low limits of detection for all elements were achieved, generally below 10 pg g −1, as well as measurement repeatability below 15%. Overall, the Na2 O2 /ICP-MS/MS method proved to be a suitable lab-based method to quickly and accurately screen rock samples originating from quartz-rich geological areas for rare earth element content; particularly useful if checking commercial viability. Highlights: Na2 O2 fusion coupled to ICP-MS/MS was used to determine REE in quartz-rich samples. The method accuracy was checked with a geological reference material and INAA. Results were within 80–98% recovery of QLO-1 reference material, comparable to INAA. Detection limits were generally below 10 pg g −1, and repeatability was below 15%. Na2 O2 /ICP-MS/MS proved to be a suitable method for REE in quartz-rich samples.